Characterization of Chondrocyte Scaffold Carriers for Cell-based Gene Therapy in Articular Cartilage Repair - Shui, Wei (2013)
Articular cartilage lesions in the knee are common injuries. Chondrocyte transplant represents a promising therapeutic modality for articular cartilage injuries. Here, we characterize the viability and transgene expression of articular chondrocytes cultured in 3-D scaffolds provided by four types of carriers. Articular chondrocytes are isolated from rabbit knees and cultured in four types of scaffolds: type I collagen sponge, fibrin glue, hyaluronan, and Open-cell PolyLactic Acid (OPLA). The cultured cells are transduced with adenovirus expressing green fluorescence protein (AdGFP) and luciferase (AdGL3-Luc). The viability and gene expression in the chondrocytes are determined with fluorescence microscopy and luciferase assay. Cartilage matrix production is assessed by Alcian blue staining. Rabbit articular chondrocytes are effectively infected by AdGFP and exhibited sustained GFP expression. All tested scaffolds support the survival and gene expression of the infected chondrocytes. However, the highest transgene expression is observed in the OPLA carrier. At four weeks, Alcian blue-positive matrix materials are readily detected in OPLA cultures. Thus, our results indicate that, while all tested carriers can support the survival of chondrocytes, OPLA supports the highest transgene expression and is the most conductive scaffold for matrix production, suggesting that OPLA may be a suitable scaffold for cell-based gene therapy of articular cartilage repairs.